Determinants of the receipt of the 9-valent human papillomavirus vaccine in the first year after introduction in North Carolina. Issue 10 (28th February 2018) - Trogdon, Justin G.; Shafer, Paul; Lindsay, Brianna; Coyne-Beasley, Tamera
Highlights: We described the transition from bi- and quadrivalent HPV vaccines to 9vHPV. The transition from other HPV vaccines to 9vHPV was relatively quick. There were disparities in the diffusion of 9vHPV across North Carolina. Abstract: Objectives: The objective of this study was to describe the transition from bi- and quadrivalent HPV vaccines to 9vHPV in aggregate and identify determinants of the receipt of 9vHPV among youth following the introduction of 9vHPV in North Carolina. Methods: The study used a retrospective cohort design with data from the North Carolina Immunization Registry (NCIR). Our sample included all doses of HPV vaccine administered between July 2015 and October 2016 to age-eligible youth (ages 9–17). We used a logistic regression model to associate individual child-level and ZIP Code Tabulation Area (ZCTA)-level characteristics with an indicator variable for receiving 9vHPV (vs. other HPV vaccines). Results: Youth receiving the HPV vaccine were more likely to receive 9vHPV if they lived in a ZCTA with a larger age-eligible (i.e., 9–17) population, a health professional shortage area, or a higher number of annual outpatient visits per capita. They were less likely to receive 9vHPV if they were older, received a publicly-funded dose, or lived in a ZCTA with a higher percentage of the population with less than a high-school education or a higher number of religious organizations. Conclusions: While the transition from other HPV vaccines to 9vHPV was relatively quick, there were disparities in the diffusion of 9vHPV across North Carolina.